Preparation of a "functional library" of African green monkey DNA fragments which substitute for the processing/polyadenylation signal in the herpes simplex virus type 1 thymidine kinase gene. - Santangelo, G M (1983)
Fragments of African green monkey (Cercopithecus aethiops) DNA (3.5 to 18.0 kilobases) were inserted downstream from the thymidine kinase (TK, tk) coding region in pTK206/SV010, a gene construct which lacks both copies of the hexanucleotide 5'-AATAAA-3' and contains a simian virus 40 origin of replication, allowing it to replicate in Cos-1 cells. No polyadenylated tk mRNA was detected in Cos-1 cells transfected by pTK206/SV010. The ability of simian DNA fragments to restore tk gene expression was examined by measuring the incorporation of [125I]iododeoxycytidine into DNA in Cos-1 cells transfected by pTK206/SV010 insertion derivatives. tk gene expression was restored by the insertion in 56 of the 67 plasmids analyzed, and the level of expression equaled or exceeded that obtained with the wild-type tk gene in 30 of these. In all plasmids examined that showed restoration of tk gene expression, polyadenylated tk mRNA of discrete size was detected. The sizes of these tk mRNAs were consistent with the existence of processing and polyadenylation signals within the inserted DNA fragments. The frequency with which inserted fragments restored tk gene expression suggests that the minimal signal for processing and polyadenylation is a hexanucleotide (AAUAAA or a similar sequence). LTK- cells were biochemically transformed to TK+ with representative insertion constructs. pTK206/SV010 transformed LTK- cells at a very low frequency; the frequency of transformation with insertion derivatives was 40 to 12,000 times higher.